Honoring Place, Detail, and Intent: A Case Study - David Ericsson (Oz, 2015)
York Mountain Winery, established in 1882, is the oldest winery in the California Central Coast region. Epoch Wines acquired the property in 2010—with ambitions to serve as patrons of the property and its iconic wine history, while adding their own layer to its ongoing use as a functioning winery.